In Vivo Degradation of Crosslinked Hyaluronic Acid Fillers by Exogenous Hyaluronidases. Issue 8 (August 2018) - Shumate, Garrett T.; Chopra, Rajesh; Jones, Derek; Messina, Darin J.; Hee, Christopher K.
Abstract : BACKGROUND: An advantage of hyaluronic acid (HA)-based fillers is reversibility. OBJECTIVE: To evaluate the ability of 2 hyaluronidases to degrade 3 HA-based fillers using a novel in vivo model . MATERIALS AND METHODS: Rats were injected with 3 HA fillers (HYC-24L+, VYC-20L, and RES-L) to create a projecting bolus. After 4 days, recombinant human hyaluronidase (HX) or ovine hyaluronidase (VIT) was administered at (1) varying doses (5 U, 10 U, or 30 U per 0.1 mL filler) or (2) different dilutions (10 U diluted 3-fold). The impact of tissue integration was assessed by administering 10 U/0.1 mL filler 4 weeks after filler injection. Three-dimensional images quantified projection loss over 72 hours. RESULTS: Complete loss of projection was achieved for all fillers with the highest HX and VIT doses; lower doses achieved less degradation. No difference in degradation was observed between HYC-24L+ and VYC-20L using HX or VIT. RES-L was slightly more degraded with 10 U VIT but not with 10 U HX. Enzyme dilution resulted in less degradation. Tissue integration did not impact the degree of degradation. CONCLUSION: This model incorporates the biological system while controlling variables including filler depth and volume and location of hyaluronidase delivery. Hyaluronic acid filler degradation by exogenous hyaluronidase was not hindered by differences among fillers.